Patients with post‐transplant biliary strictures have significantly higher rates of liver transplant failure and rejection: A nationwide inpatient analysis. Issue 7 (12th January 2021) - Kohli, Divyanshoo R; Desai, Madhav V; Kennedy, Kevin F; Pandya, Prashant; Sharma, Prateek
Abstract: Background and Aim: Biliary strictures are a common complication of liver transplantation. We assess the impact of post‐transplant biliary strictures and describe the outcomes of endoscopic retrograde cholangiopancreatography (ERCP), interventional radiology (IR), and surgical therapies. Methods: Using the Nationwide Readmissions Database (NRD), hospitalized liver transplant recipients were identified using the International Classification of Diseases 10th Revision codes. Patients with post‐transplant biliary strictures were identified, and outcomes (inpatient mortality, 30‐day readmission, transplant rejection/infection/failure, and disposition) were compared with transplant recipients without strictures. Among transplant patients with biliary strictures who underwent therapeutic intervention, corresponding outcomes were compared between IR, surgical interventions, and ERCP. Results: Of the 8300 liver transplant recipients meeting selection criteria, 554 patients (age 48.9 ± 18.2 years, mean ± SD; 39.5% women) had biliary strictures. Compared with patients without strictures, the adjusted odds ratio (OR) for various outcomes in patients with biliary strictures were as follows: 1.46 (1.20, 1.77; P < 0.001) for 30‐day non‐elective readmission, 2.71 (2.04, 3.59; P < 0.001) allograft rejection, 2.32 (1.61, 3.37; P < 0.001) liver transplant failure, 3.05 (1.39, 6.73; P < 0.01) infection, and 1.41 (1.08, 1.82; P = 0.01) disposition to skilled nursing or intermediate care facility. Therapeutic interventions during index hospitalization were performed in 350 patients: ERCP 46.6% ( n = 163), surgery 41% ( n = 144), and IR 12.3% ( n = 43) patients. Compared with ERCP, the adjusted odds for various outcomes were disposition to skilled nursing or intermediate care facility 2.72 (1.08, 6.87; P = 0.03) and 2.09 (1.05, 4.15; P = 0.036), prolongation of hospitalization 14.4 (3.7, 25.1; P = 0.008) and 15.0 (7.4, 22.7; P < 0.001), and failure of liver allograft 8.47 (1.47, 48.6; P = 0.017) and 12.23 (2.74, 54.4; P = 0.001) for IR and surgical interventions, respectively. Conclusion: Post‐liver transplant biliary strictures are associated with increased rates of allograft rejection, allograft failure/infections, and readmissions. Compared with ERCP, management of these patients with IR or surgical interventions is associated with significantly higher rates of allograft failure and hospital stay.